2017
DOI: 10.4338/aci-2016-09-ra-0153
|View full text |Cite
|
Sign up to set email alerts
|

Examining Perceptions of Computerized Physician Order Entry in a Neonatal Intensive Care Unit

Abstract: Introducing CPOE is a potentially risky endeavor and must be done carefully to mitigate harm. Although high expectations of the system can be met, it is important to attend to differing expectations among clinicians with varied levels of comfort with technology. Interdisciplinary collaboration is critical in planning a functioning CPOE to ensure that efficient workflow is maintained and appropriate supports for individuals with a lower degree of technical literacy is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Most studies (35 studies) were conducted in the US, 1 in the United Kingdom, 17 and 2 were multinational as systematic reviews. 10 , 43 Study designs included cross-sectional studies (4 studies), 27 , 65 , 92 , 93 pre-post-intervention surveys (21 studies), 17 , 22 , 28–30 , 35 , 44–46 , 49 , 51 , 56 , 57 , 63 , 64 , 66 , 67 , 76 , 77 , 83 prospective studies (5 studies), 20 , 32 , 41 , 62 , 70 randomized controlled trials (RCTs) (4 studies), 39 , 58 , 59 , 75 2 systematic reviews 10 , 43 and other designs (2 studies). 14 , 53 Comparators were a condition of study inclusion, and the majority of studies provided baseline or preintervention data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies (35 studies) were conducted in the US, 1 in the United Kingdom, 17 and 2 were multinational as systematic reviews. 10 , 43 Study designs included cross-sectional studies (4 studies), 27 , 65 , 92 , 93 pre-post-intervention surveys (21 studies), 17 , 22 , 28–30 , 35 , 44–46 , 49 , 51 , 56 , 57 , 63 , 64 , 66 , 67 , 76 , 77 , 83 prospective studies (5 studies), 20 , 32 , 41 , 62 , 70 randomized controlled trials (RCTs) (4 studies), 39 , 58 , 59 , 75 2 systematic reviews 10 , 43 and other designs (2 studies). 14 , 53 Comparators were a condition of study inclusion, and the majority of studies provided baseline or preintervention data.…”
Section: Resultsmentioning
confidence: 99%
“… 39 , 70 Interventions were conducted in multiple settings, but most evaluated primary care (22 studies) physicians and residents. 20 , 22 , 27–30 , 32 , 39 , 41 , 44–46 , 56 , 58 , 59 , 64 , 65 , 70 , 77 , 83 , 92 , 93 Some studies examined specialists (7 studies), 14 , 35 , 53 , 57 , 63 , 66 , 75 a mix of primary care physicians and specialists (4 studies), 10 , 21 , 62 , 76 and groups of physicians with unspecified specialties (5 studies). 17 , 43 , 49 , 51 , 67…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They store and organize a large amount of clinical data (i.e., vital signs, laboratory data), provide clinical decision support systems to assist clinicians in making medical decisions, prevent medication errors, and allow order entry anywhere there is a computer. [10][11][12][13] Furthermore, some studies have shown that EHRs are associated with lower mortality rates and complications. 10,12,[14][15][16] But, while EHRs are necessary to deliver medical care, they do not replace it.…”
Section: Discussionmentioning
confidence: 99%
“…While the impact of HIT on test-result management practices in Emergency Department (ED) settings has been studied, [7][8][9] the effect of HIT specifically on Intensive Care Unit (ICU) test-result management has not yet been examined, with ICU studies predominantly assessing the impact of CPOE on clinicians or medication management. 10,11 Despite the availability of sophisticated computerised systems, missed test-results and inadequate test-result follow-up continue to impact patient safety and quality of care. 6,[12][13][14][15][16] In 2017, the US ECRI Institute identified 'Test-result Reporting and Follow-Up' as a top 10 patient safety concern.…”
Section: Introductionmentioning
confidence: 99%